2012
DOI: 10.1007/s10995-012-1030-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age and Low Birth Weight: A Reinterpretation of Their Association Under a Demographic Transition in Southern Brazil

Abstract: To evaluate the relationship between changes in fecundity rates and maternal age and the impact of maternal age on low birth weight (LBW) rates in a developed region in southern Brazil. A time series study evaluating birth weight and maternal ages through the born alive information system (SINASC) in Porto Alegre from 1996 to 2008. The Chi-square test for trends was used to evaluate the trend of LBW and fecundity rates at each maternal age. Population attributed risk (PAR) was used to calculate the impact of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…CD offspring were also more likely to have greater educational achievement. This finding is in accordance with a study in Brazil, which showed that there has been a change in maternal age distribution toward older mothers accompanied by an increasing low-birth-weight rate (35). Other researchers proposed that the introduction of live saving technologies, such as CD, reaches initially the most-privileged social strata (e.g., high-schooling mothers) (36,37).…”
Section: Discussionsupporting
confidence: 89%
“…CD offspring were also more likely to have greater educational achievement. This finding is in accordance with a study in Brazil, which showed that there has been a change in maternal age distribution toward older mothers accompanied by an increasing low-birth-weight rate (35). Other researchers proposed that the introduction of live saving technologies, such as CD, reaches initially the most-privileged social strata (e.g., high-schooling mothers) (36,37).…”
Section: Discussionsupporting
confidence: 89%
“…Such a shift in demographic properties of a population in favor of high risk age groups has been observed elsewhere. In Brazil a similar situation in fertility dynamics and in-creasingly delivery at older maternal age above 34 years was observed in one province and had contributed significantly to increased poor pregnancy outcomes such as low birth weight deliveries [26].…”
Section: Discussionmentioning
confidence: 65%
“…Low birth weight has proved difficult to control among teenagers as proven by the high incidence across countries regardless the level of economical development [13,26,27]. The importance of low socio-economic status of this age group in the causation of low birth weight has been suggested by some studies [1,2] but not by others [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in the number of adolescent pregnancy in Brazil has been notable in recent years; [ 25 , 41 ] however, high rates are still a concern, mainly in regions of higher socioeconomic vulnerability [ 18 ]. In this study, adolescent mothers are an important factor for LBW, especially in the North, Northeast, and Central West regions, presenting lower socioeconomic development.…”
Section: Discussionmentioning
confidence: 99%